Natural Drugs from Plants - El-Shemy, Hany A. (IntechOpen, 2022)
Natural Drugs from Plants emphasizes the importance of medicinal plants for drug discovery worldwide. Chapters discuss the active ingredients of certain medicinal plants, their mechanisms of action, and how they can be used to treat different diseases.